Annihilating Difference : The Anthropology of Genocide - Hinton, Alexander Laban (Book collections on Project MUSE., 2002)
This text presents a collection of original essays on genocide. It explores a wide range of cases, including Nazi Germany, Cambodia, Guatemala, Rwanda, and Bosnia.